Factors affecting the work performance of civil servants in the Department of Social Services in West Sumatra - Akmal, Akmal (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Clark, C. S., Dobbins, G. H., & Ladd, R. T. (1993). Exploratory Field Study of Training Motivation: Infiluence of Involvement, Credibility, and Transfer Climate. Group & Organization Management, 18(3), 292–307. https://doi.org/10.1177/1059601193183003 Fernandez, S., & Moldogaziev, T. (2010). Empowering Public Sector Employees to Improve Performance: Does It Work? The American Review of Public Administration, 41(1), 23–47. https://doi.org/10.1177/0275074009355943 Hasibuan, M. (2020). Sumber Daya Manusia. Bumi Aksara. Hayati, K., & Caniago, I. (2012). Islamic Work Ethic: The Role of Intrinsic Motivation, Job Satisfaction, Organizational Commitment and Job Performance. Procedia - Social and Behavioral Sciences, 65, 272–277. https://doi.org/https://doi.org/10.1016/j.sbspro.2012.11.122 Jais, A. (2017). Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Prestasi Kerja Pegawai pada Rumah Sakit Umum Daerah H. Andi Sulthan Daeng Radja Kabupaten Bulukumba. UIN Alauddin Makassar. Kartini, K. (2017). Pemimpin dan Kepemimpinan. Rajawali Press. Mangkunegara, A. (2017). Manajemen Sumber Daya Manusia Perusahaan. Remaja Rosdakarya. Nawawi, H. (2017). Perencanaan SDM untuk Organisasi Profit yang Kompetitif. UGM Press. Ong, J. O., & Mahazan, M. (2020). Strategi Pengelolaan SDM dalam Peningkatan Kinerja Perusahaan Berkelanjutan di Era Industri 4.0. Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2(1), 159–168. https://doi.org/10.21512/becossjournal.v2i1.6252 Rivai, V. (2018). Manajemen Sumber Daya Manusia untuk Perusahaan: dari Teori ke Praktik. Raja Grafindo Persada. Robbins, P., & Coutler, M. (2017). Human Resources Management. Salemba Empat. Siagian, S. (2018). Manajemen Sumber Daya Manusia. Bumi Aksara. Sinambela, L. (2017). Reformasi Pelayanan Publik. Bumi Aksara. Sunarsi, D. (2018). Pengaruh Gaya Kepemimpinan, Motivasi dan Disiplin Kerja terhadap Kinerja Pendidik Yayasan Marvin. Inovasi, 5(1), 1–18. https://doi.org/10.32493/inovasi.v5i1.y2018.p1-18 Sunyoto, D. (2018). Manajemen Sumber Daya Manusia. Center for Academic Publishing Service. Sutrisno, E. (2017). Manajemen Sumber Daya Manusia. Kencana ( Prenadamedia Group). Thoha, M. (2018). Perilaku Organisasi: Konsep dan Dasar Aplikasi. Raja Grafindo Persada. Timpe, A. (2017). Memotivasi Pegawai. Elex Media Komputindo.